Hubungan Screen Time dan Kualitas Tidur dengan Kebugaran Kardiorespirasi pada Mahasiswa Pendidikan Dokter UIN Alauddin Makassar - Putri Auliah Zahrani; Trisnawaty; Miswani Mukani Syuaib; Takdir; Halimah Sa’diyah (Alami Journal (Alauddin Islamic Medical) Journal, 2024)
Modern lifestyles, which tend towards instant satisfaction, have significantly influenced society, leading to an increasing trend toward unhealthy lifestyles. This research aimed to find out the relationship between screen time and sleep quality with cardiorespiratory fitness in medical students at UIN Alauddin Makassar. The research design in this study was quantitative with a cross-sectional approach. The population in this study was preclinic medical education students at UIN Alauddin Makassar. The samples were chosen with the purposive sampling technique with 140 samples. Data was collected by filling out a form in the Questionnaire Screen Time of Adolescents (QueST) for screen time, the Pittsburgh Sleep Quality Index (PSQI) questionnaire for sleep quality and cardiorespiratory fitness measured by carrying out the Harvard Step Test. Data were analyzed using univariate and bivariate tests and the Spearman rho test in the SPSS application. The results of bivariate analysis between the variables screen time and sleep quality showed that screen time had a p-value of 0.000 (p < 0.05) and sleep quality had a p-value of 0.000 (p < 0.05). In conclusion, there was a significant relationship between screen time, sleep quality and cardiorespiratory fitness in medical students at UIN Alauddin Makassar.